Linguistic complexity in L2 writing revisited: Issues of topic, proficiency, and construct multidimensionality. (June 2017) - Yoon, Hyung-Jo
Abstract: This study aims to explore the validity of syntactic, lexical, and morphological complexity measures in capturing topic and proficiency differences in L2 writing. The additional purpose of this study is to examine how these measures gauge distinct dimensions of complexity. To these ends, this study examined a corpus of 1198 argumentative essays on two different topics written by college-level Chinese EFL learners. The essays were analyzed for topic effects (within-subjects) and for development across proficiency levels (between-subjects), as well as for the multidimensional construct of complexity. The result indicated strong topic effects on the majority of complexity measures (i.e., more complex language in a topic more relevant to writers' experiences). There were significant changes across proficiency levels in phrase-level syntactic, lexical, and morphological measures but not in clause-level measures. Last, a factor analysis result showed that lexical and morphological dimensions of complexity loaded on one construct and that the unit-length measures with different base units loaded on different constructs. The results of this study are interpreted in terms of topic relevance and the validity of multidimensional dimensions of complexity.